Structure Simulation on Portable Commuter Bike Considering Frame Design and Materials Alternatives - Bambang Iskandriawan (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Portable commuter bikes (PCBs) are needed by commuters, people who live in the suburbs of a city and whose activities are in the middle of the city or vice versa, even for longer distances. For user safety, it is mandatory to check the strength aspect of the bicycle frame structure. PCBs are not only ridden by the commuter but can also be folded to bring them along on public transportation. The PCB design also included a stool to be used by the commuter while waiting for the bus or train. The strength of the PCB structure was investigated using numerical simulations based on static load. The displacements and stresses were controlled using a variety of PCB frame designs and materials. The results of this bicycle structural inspection can guide the improvement of PCB designs in the future.